2020
DOI: 10.1002/jrs.5991
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical treatment of single‐molecule scanning Raman picoscopy in strongly inhomogeneous near fields

Abstract: Tip‐enhanced Raman spectroscopy (TERS) of a single molecule is commonly described by considering the change in the polarizability of the molecule with respect to a normal coordinate induced by homogeneous illumination. However, the local fields induced by nanoscale and atomic‐scale features at the surface of metallic clusters and nanogaps show strong inhomogeneities in their spatial distribution, which induces breaking of Raman selection rules. In this context, the spatial extension of the molecular electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
(105 reference statements)
0
21
0
Order By: Relevance
“…For the single molecule interacting with this atomic-scale plasmonic feature, SERS is further amplified by its extra enhancement of the local field E nano in the NPoM gap (E/E nano ) 4 ∼ 10 1 −10 4 while also inducing a strong field gradient over the molecule leading to broken selection rules. 26 This leads to the characteristic appearance of nominally dark SERS modes in picocavity spectra and allows for the single molecule SERS to be spectrally isolated from the persistent signal from all other molecules. This transient SERS is used to probe the underlying nanocavity field profiles through simultaneous continuous wave excitation using two wavelengths (λ 1 = 633 nm, λ 2 = 785 nm).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the single molecule interacting with this atomic-scale plasmonic feature, SERS is further amplified by its extra enhancement of the local field E nano in the NPoM gap (E/E nano ) 4 ∼ 10 1 −10 4 while also inducing a strong field gradient over the molecule leading to broken selection rules. 26 This leads to the characteristic appearance of nominally dark SERS modes in picocavity spectra and allows for the single molecule SERS to be spectrally isolated from the persistent signal from all other molecules. This transient SERS is used to probe the underlying nanocavity field profiles through simultaneous continuous wave excitation using two wavelengths (λ 1 = 633 nm, λ 2 = 785 nm).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…144 A recent theoretical work combined DFT and classical calculations to map the Raman behavior of single molecules in strongly inhomogeneous fields, and demonstrated that picocavities are capable of probing and revealing "intramolecular features of a single molecule in real space". 145 Hence, picocavities provide unprecedented access to specific chemical bonds within a single molecule, opening pathways to modulate and to control optically specific intramolecular bonds and siteselective chemistry. 141 Although thus far picocavities have been used to access vibrational modes at the submolecular level, they have the potential to offer extraordinary control over catalytic reactions at the single-molecule level as well.…”
Section: Atomic-scale Plasmonics For Catalysismentioning
confidence: 99%
“…Since then, other tip-based techniques with atomic light confinement have been reported, achieving angstrom resolution for imaging the normal modes and intramolecular charges/currents in single molecules, using either the Raman signal emerging from specific chemical bonds , or photoluminescent measurements at the submolecular level . Recent theoretical work combined DFT and classical calculations to map the Raman behavior of single molecules in strongly inhomogeneous fields and demonstrated that picocavities are capable of probing and revealing “intramolecular features of single molecules in real space” . Hence, picocavities provide unprecedented access to specific chemical bonds within a single molecule, opening pathways to modulate and to control optically specific intramolecular bonds and site-selective chemistry …”
Section: Atomic-scale Plasmonics For Catalysismentioning
confidence: 99%
“…Aizpurua et al introduce a general treatment to simulate single‐molecule TERS spectra and the corresponding energy‐filtered vibrational fingerprint maps, wherein the polarization properties of the single molecule and that of the optical enhancing nanoresonator can be calculated separately and then conveniently combined to obtain the total Raman cross section of the molecule when there is a strongly inhomogeneous field. [ 4 ]…”
Section: Theorymentioning
confidence: 99%
“…[3] Aizpurua et al introduce a general treatment to simulate single-molecule TERS spectra and the corresponding energy-filtered vibrational fingerprint maps, wherein the polarization properties of the single molecule and that of the optical enhancing nanoresonator can be calculated separately and then conveniently combined to obtain the total Raman cross section of the molecule when there is a strongly inhomogeneous field. [4] Reich et al review a number of experimental studies examining the predictions of the electromagnetic enhancement theory of SERS and focusing on the results that require going beyond simple electromagnetic enhancement theory. The authors argue that the results of these experiments reveal the need to develop the theory of SERS further, especially the exact role of plasmonic enhancement in inelastic light scattering.…”
Section: Theorymentioning
confidence: 99%